Examination of uric acid levels in Karonsih, Semarang: invasive and non-invasive approaches based on research - Heni Sumarti; Irman Said Prastyo; Rina Susi Cahyawati; Istikomah; Ice Uliya Sari; Mohammad Candra Malindo (Community Research and Application Journal (CRAJ), 2024)
Regularly monitoring uric acid levels is essential for preventing and managing gout, where excess uric acid accumulates in joints and causes pain and swelling. Traditionally, invasive blood sample methods are used for this measurement, which can be uncomfortable and increase medical waste. This community service project, organized by the Physics Department of Universitas Islam Negeri Walisongo Semarang in collaboration with the Ngabdi Neliteni Ngabekti (N3) community organization, compares invasive and non-invasive approaches for uric acid level assessment among residents in Karonsih, Semarang. A newly developed non-invasive device was evaluated alongside standard invasive methods based on participant comfort, accuracy, and feedback. Results indicate that, although the non-invasive device showed a mean error rate of 40.52%, it was preferred for its comfort and non-invasive nature. These findings highlight the potential of non-invasive technology in community health monitoring and underline the importance of regular health check-ups facilitated by collaborations between community organizations, educational institutions, and government bodies.